2011
DOI: 10.1108/00907321111186695
|View full text |Cite
|
Sign up to set email alerts
|

Librarian perceptions and information literacy instruction models

Abstract: Purpose-This paper explores both instruction librarians' attitudes on teaching and how they identify themselves as teachers. Particular attention is paid to teaching librarians' views on the effectiveness of two types of instruction models: for-credit courses and course-integrated library instruction. Design/methodology/approach-To investigate librarians' attitudes towards these two models, a survey was constructed targeting librarians who teach information literacy (IL). Findings-The results indicate that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
1
13
1
Order By: Relevance
“…The methods academic librarians use for instruction on information literacy varies. Various methods include a one-shot instruction session, for-credit courses, embedded information literacy, and interactions at the reference desk (Davis, 2007;Davis et al, 2011;Roy & Hensley, 2016;Zai, 2014). Librarian 1 mentioned that she did not see herself as a teacher because she was not with the students for a full semester.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods academic librarians use for instruction on information literacy varies. Various methods include a one-shot instruction session, for-credit courses, embedded information literacy, and interactions at the reference desk (Davis, 2007;Davis et al, 2011;Roy & Hensley, 2016;Zai, 2014). Librarian 1 mentioned that she did not see herself as a teacher because she was not with the students for a full semester.…”
Section: Discussionmentioning
confidence: 99%
“…The Scholarship of Teaching and Learning (SoTL) may be a vehicle through which academic librarians develop a cohesive identity. Previous research has shown that a professional identity is missing from the field of librarianship (Davis, Lundstrom, & Martin, 2011;Freedman, 2014;Walter, 2008). Often, librarians are viewed as caretakers of resources.…”
mentioning
confidence: 99%
“…The survey's premise assumes that credit-bearing IL is being offered, so results report on practical aspects of this type of effort, including assessment efforts, course development and philosophy, adjunct use, and more. 9 Erin Davis, Kacy Lundstrom, and Pamela Martin conducted a 2011 survey of academic librarians who participate in library instruction by drawing on followers of three ALA-sponsored listservs whose readers are likely to be teaching librarians: ILI-L, COLLIB-L, and STS-L. Their findings dealt with these librarians' perceptions of their self-identity and their attitudes about the different "models" or methods of library instruction. Approximately 37 percent of the respondents offer for-credit courses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the ubiquity of one-shot instruction methods in the literature, some librarians are skeptical of them. Davis, Lundstrom & Martin (2011), who detail the arguments for both one-shot instruction sessions and credit courses, found that over 50% of the librarians in their study were neutral as to which is a more effective method for teaching information literacy. Some researchers laud the effectiveness of reference services; Johnson & Lindsay (2006) and Cull (2005) found that their survey respondents considered reference work the most effective way of teaching information literacy to students, because it is focused on a student's individual needs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Others advocate for the effectiveness of credit courses (Davis, Lundstrom & Martin, 2011;Partello, 2005). Some authors argue that one-shot instruction sessions can be effective, but are improved by using active learning techniques in place of the traditional lecture and demonstration (Hollister & Coe, 2003), and that their effectiveness depends heavily on effective collaboration with subject faculty (Derakhshan & Singh, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%